Gamma radiation production using channeled positron annihilation in crystals. (12th June 2015) - Gevorkyan, A S; Oganesyan, Koryun B; Rostovtsev, Yuri V; Kurizki, Gershon
Abstract: The possibility of channeling low-energy relativistic positrons in some ionic crystals with axial symmetry is shown. The annihilation processes of positrons with medium electrons are investigated in detail. The lifetime of a positron in the regime of channeling is estimated; the existence of a long relaxation lifetime has been shown.